Bez sentymentow - Segal, Erich, 1937-; Nowakowski, Witold (Warszawa : Wydawn. ALBATROS : A. Kurylowicz, 2001)
Polish translation of "No Love Lost". The story of a couple who, because they are infertile, adopt a young boy. From this point their lives change dramatically.
Translation of: No love lost.
Keywords: Adoption -- Fiction; Adoptive parents -- Fiction